63 Hypoxia induces gene-specific epigenetic modifications in human cardiac fibroblasts which are associated with the development of myocardial fibrosis. (5th October 2017) - Glezeva, N; Das, S; Moran, B; Ledwidge, M; McDonald, K; Baugh, J; Watson, C
Abstract : Introduction: Ischemia caused by coronary artery disease and myocardial infarction leads to aberrant ventricular remodelling and cardiac fibrosis. This occurs partly through accumulation of gene expression changes in resident fibroblasts, resulting in an overactive fibrotic phenotype. We have recently shown that human myocardial tissue hypoxia is associated with an enhanced pro-fibrotic gene profile in the tissue and, more significantly, that hypoxia-induced pro-fibrotic changes in cardiac fibroblasts are associated with global DNA hypermethylation. Based on this epigenetics data, we have conducted a gene-specific methylation study to investigate methylation changes that occur in hypoxic ventricular fibroblasts and to gain novel insights into pathways and mechanisms that may contribute to post-ischemic cardiac remodelling. Methods: Human ventricular cardiac fibroblasts were exposed to 1% oxygen for up to 8 days. Global methylation changes were assessed using anti-5-methylcytosine (5 MeC) staining, flow cytometry, QPCR, and western blot. Gene-specific methylation changes associated with hypoxia and an increased fibrotic state were determined by 5 MeC immunoprecipitation and GeneChip human promoter arrays (Affymetrix), and validated by bisulphite genomic sequencing (BGS). Gene functional classification and pathway analysis were performed (DAVID, FUNRICH). Results: Hypoxia-induced pro-fibrotic changes in cardiac fibroblasts included increased cell proliferation and increased alpha smooth muscle actin, collagen 1, DNMT1 and DNMT3 B expression which associated with global DNA hypermethylation. Array analysis revealed 32 gene-specific hypermethylation changes and 101 hypomethylation changes occurred in hypoxia. Fifteen pathophysiologically relevant genes (5 hypermethylated, 10 hypomethylated) were identified by functional classification and pathway analysis to have a role in cardiac fibrosis, extracellular matrix remodelling, transforming growth factor beta signalling, cell proliferation, wound repair, ischemia, hypertension, hypertrophy, and heart failure. These are being validated using bisulphite genomic sequencing. Conclusion: Epigenetic modifications and changes in the epigenetic machinery identified in cardiac fibroblasts during prolonged hypoxia may contribute to the pro-fibrotic nature of the ischemic milieu in the heart during disease. The application of epigenetic based therapy, such as DNA methylation modifiers, as a treatment option for cardiac pathologies associated with fibrosis and ischemia may provide therapeutic benefit.